ANALISIS PENGARUH PENGUNGKAPAN ISLAMIC CORPORATE GOVERNANCE DAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Hatta Setiabudhi (Jurnal Riset Keuangan dan Akuntansi, 2022)
The purpose of this study to provide empirical evidence of the influence disclosure of Islamic Corporate Governance and Islamic Corporate Social Responsibility on financial performance of Islamic Bank in Indonesia. This study used secondary data which analyzed with regression analysis. This study used annual report data from 2013-2017 which published in each Islamic Bank sample in this study. The regression results analysis showed that the disclosure of Islamic Corporate Governance, and Islamic Corporate Social Responsibility have no significant effect on financial performance in Indonesia. Keywords:  Islamic Corporate Governance, Islamic Corporate Social Responsibility, Financial Performance